Forecasting of multivariant changes in Step test under the influence of natural adaptogens - Walery Zukow; Igor-Severyn Flyunt; Sofiya Ruzhylo; Halyna Koval'chuk; Yaryna Nahurna; Dariya Popovych; Serhiy Sarancha (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2021)
Background. Earlier, we found the multivariant nature of the Popovych's step test change in children after a course of adaptogenic balneotherapy. In particular, the step test improved in 53,7% of children, remained unchanged in 28,8%, and worsened in 17,5%. The purpose of this study is to identify predictors that allow us to forecast each variation of the step test. Material and methods. Object of observation was 80 children of both sexes, ages 10-17, arriving at the clinical sanatorium "Dzherelo" of Truskavets' spa from radionuclide contaminated territories. The main parameter of the study was the Popovych's step test. State of autonomous nervous, endocrine and immune systems was assessed as well as others functional and metabolic tests. Results. Discriminant analysis was subsequently applied to identify constellations of parameters-predictors of each variant of change in step test. The program selected 16 initial parameters as predictors (primarily level of step test, next sex, body mass and temperature, levels of Gench's and Teslenko's tests, vagal tone, erythrocytes sedimentation rate, trombocytes level as well as 7 immune parameters). The correctly of forecasting of the positive actotropic effect is 90,7%; of neutral is 78,3%; of negative is 92,9%, and total correctness is 87,5%. Conclusion. Balneotherapy causes multivariate changes in Popopvych's step test, which determined by constellation of 16 initial parameters.